2018
DOI: 10.4149/bll_2018_041
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered mesenchymal stromal cells in cancer gene therapy

Abstract: Based on our experimental data, we aimed to emphasise the perspectives of the use of mesenchymal stromal cells (MSC) in the cancer gene therapy. On the other hand, we would like to point out factors which should be taken into consideration at their clinical use. In this review we defi ne MSC as unique targets for targeted therapy. We proved the effi cacy of experimental therapeutic approach utilising enzymatic conversion of non-toxic prodrug into chemotherapeutic by engineered MSC, and we observed signifi cant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The therapeutic potential of MSCs has been explored in a number of phase I, II, and III clinical trials [23], of which several were targeted against graft versus-host disease and to support engraftment of hematopoietic stem cells [24, 25]. Yet, very few of these trials use MSCs to treat tumor diseases [23, 26, 27], such as gastrointestinal, lung, and ovarian cancer. As for the study targeting ovarian cancer, MSCs expressing cytokines were used as therapeutic payload [23] and were derived from bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic potential of MSCs has been explored in a number of phase I, II, and III clinical trials [23], of which several were targeted against graft versus-host disease and to support engraftment of hematopoietic stem cells [24, 25]. Yet, very few of these trials use MSCs to treat tumor diseases [23, 26, 27], such as gastrointestinal, lung, and ovarian cancer. As for the study targeting ovarian cancer, MSCs expressing cytokines were used as therapeutic payload [23] and were derived from bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs tend to differentiate down mesodermal lineages, however, under appropriate stimuli, it has been suggested that MSCs are capable of differentiation into tissues of endodermal and neuroectodermal lineages [42]. As MSCs are self-renewing cells with immunomodulatory properties and the ability to be differentiated into several lineages [46][47][48][49] they are a vital resource for tissue engineering, regenerative medicine, and cell-based therapy research [39,46,50].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In recent studies, gene therapy has been discussed as a potentially promising way to treat cancers, but the problems are how to guide genes to the tumor site(s) or which vehicle can selectively find cancer location and which vehicle can be stable in the tumor microenvironment (3). The ongoing process of research has shown that mesenchymal stem cells can be a noticeable strategy in anticancer therapies (4).…”
Section: Introductionmentioning
confidence: 99%